Athletes’ dispositional self-control, and their perceived influence of officials on their anxiety levels - Raffeei, Nurhakimah (2016)
In the sporting context, the study of stress has been largely themed around the anxiety-performance relationship. Although this relationship has been traditionally understood as negatively related, anxiety can also have a facilitative effect on performance. To this end, self-control plays a mediating role as it can help athletes channel the anxiety stimulus towards a more positive performance outcome. Studies have shown that athletes rely on informational cues to form impression of officials and that the latter represent as a highly rated source of stress. Despite this, the athlete-official relationship has been largely unexplored. As such, this study aims to investigate if athletes group meaningfully based on trait characteristics (self-control & anxiety) & whether they predispose athletes to perceive cues emitted by officials as salient in affecting their state anxiety. 147 athletes aged 18 to 34 years-old (Mage = 23.05, SDage = ± 3.98) from territorial/invasion sports participated in this research. They were administered a compiled set of scales & questionnaire measuring trait characteristics & state anxiety. Hierarchical cluster analysis revealed that athletes clustered in three distinct groups based on trait characteristics – 1. High Control, Low Anxiety (HCLA), 2. Low Control, High Anxiety (LCHA), 3. Low Control, Low Anxiety (LCLA). Additionally, these clusters had unique responses to perception of officials as influential in their state anxiety. In particular, the HCLA cluster rated these cues as least influential compared to the other two clusters. Therefore, the results suggests that possessing these trait characteristics do affect an athlete’s perceived influence of official on state anxiety.